Psychometric properties the of Brazilian Portuguese version of Snaith-Hamilton Pleasure Scale (SHAPS) - Jesus-Nunes, Ana Paula (Trends Psychiatry Psychother, 2021)
INTRODUCTION: Anhedonia is defined as the reduced ability to feel pleasure and is a core symptom of various psychiatric disorders such as depression and schizophrenia. The Snaith-Hamilton Pleasure Scale (SHAPS) was developed to assess the presence of anhedonia. The objective of this study was to assess the psychometric properties of the Brazilian Portuguese version of the SHAPS. METHODS: In this study, the SHAPS (14 items) was translated into Brazilian Portuguese and validated using data obtained from 228 subjects within a clinical sample. Psychometric properties were assessed using item response theory (logistic models) and classical test theory (Cronbach’s alpha). We checked for external validity using a non-parametric correlation with an independent scale: Hospital Anxiety and Depression Scale – Depression subscale (HAD-D). RESULTS: The SHAPS presented good internal consistency, with a Cronbach’s α coefficient of 0.759 and adequacy to an IRT 1 parameter logistic (Rasch) model. The SHAPS presented significant correlation with the external measure HAD-D, with Spearman’s ρ = 0.249 (S = 1368914; p < 0.001). CONCLUSION: These results suggest that the Brazilian Portuguese version of the SHAPS is a reliable and valid instrument to assess hedonic tone.